If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(2x-3)=4x-16
We move all terms to the left:
2(2x-3)-(4x-16)=0
We multiply parentheses
4x-(4x-16)-6=0
We get rid of parentheses
4x-4x+16-6=0
We add all the numbers together, and all the variables
10!=0
There is no solution for this equation
| 5n=2-3/4 | | 4x+1.7=6.9 | | 52=4/5r | | (t+15)^2+5=0 | | 3751+5=c | | -5k+23=133 | | 5(2x+6)+x=4(x+2) | | 21+1/3=3m-(2+2/3) | | z/6+6=8-z/ | | 2/3=x/3.5 | | 1(1/8)=g-4(2/5) | | 5-8(1-8)-9x= | | 3x-17x-7=-2/3(6x-30)+6 | | I=0.08x+(.18)(11000-x) | | -6(z+1)=-3-(6z+3) | | 7/2=b+9/5 | | m/3=5/2 | | x+2/x-2-8/x^2-2x=2/x | | -5x+3x+1=-14 | | C=37.51+0.5x | | x+2/x-2-8/x^2-2x=2/2 | | 4-2x=-32 | | 25n^2+75n=-56 | | -x/2-7=1 | | -x/5-4=-5 | | C=37.51+0.50x | | 10-(-2x+1)+4=-19(x+1) | | -x/6+6=0 | | ∣∣∣1x52∣∣∣=−13 | | 3(x+7)=x-3 | | 1-(-2x+1)+4=-19(x+1) | | -8=x÷-2-6 |